Sobre «La miseria del mundo» de Pierre Bourdieu: un análisis de las consecuencias sociales de la globalización económica en el primer mundo - Pérez Medina, Juan Carlos (Cuadernos de Trabajo Social, 2006)
Pierre Bourdieu (1932-2002), French sociologist whose work has important influence both on sociological theory and in social and political arenas, published «Poverty in the World» in 1993. Together with a team of collaborators, among whom are sociologists like Loïc Wacquant or Patrick Champagne, Bourdieu shows us an important compilation of in-depth interviews conducted with a broad spectrum of individuals. In these interviews, he studies the repercussions of the new economic and socio political situation on their lives. «Poverty in the World» seeks to reveal the structural relationships underlying different situations of «social poverty«, which form part of the daily life of thousands of ordinary citizens at different social levels in France in the nineties. Within their pages appear suburban youth, workers who retired early, teachers and social workers, immigrants of different generations, police officers, magistrates, businessmen… It is not a portrait of «dire poverty«, but rather the «difficult places» where, like the doctor confronting illness, the sociologist must go beyond the «symptoms» shown by the mass media or political discourse to make inquiries about the underlying authentic dialectic relationships, making visible the invisible in a consequential work of the social scientist in the world in which he lives. Pierre Bourdieu is one of the social scientists who most stood out in the political arena, especially in the last phase of his public life, where he sought to place his theoretical analyses at the service of the social problems of his day. His analyses continue being valid in contemporary situations, such as the riots that took place in the French slums last autumn.